(untitled) (Journal of Economic Research & Business Administration, 2018)
Measuring competitiveness offers hundreds of analytical options. We have chosen to analyze and compare companies of confectionery sector in Kazakhstan. We opted to use bankruptcy models and compare competitiveness through the financial situation of main competitors on that market. Companies analyzed comprise of two Ukrainian companies (Konti and Roshen), Russian companies (Nestlé Russian branch serving also Central Asian markets and KDV – Yaskino) and three local corporations Rakhat, Bayan Sulu and Konfety Karagandy. Models used for analysis are Altman z-score model, Taffler z-score model, IN99, IN01, IN05 models. The IN models were created in the Czech Republic based on companies’ data from the 1990s which was the period of higher inflation, small currency an big banking crisis, massive imports, developing competition and infrequent political turmoil. These models have comparably much greater benefits for analyzing companies in Kazakhstan because they are based on hundreds of companies in contrast to tens of companies on which Altman or Taffler based their famous and highly predictive models. We present an analysis of models in 2007 – 2016 period based on publicly accessible data. We show the IN models have valuable benefits for comparison compared with other older models and that they can disclose certain events or corporate situations in a clearer way than other Altman or Taffler z-score models and should be used in Kazakhstan and improved to suit better the local market environment.